The changing landscape of nephrology physician assistants and nurse practitioners. Issue 1 (January 2021) - Davis, Jane; Zuber, Kim
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Background: Physician assistants (PAs) and nurse practitioners (NPs) have expanded roles in nephrology as both the patient load and acuity of care needed for this population have increased. Purpose: To evaluate workforce patterns of PAs and NPs working in nephrology over the past decade. Methods: Using the biannual survey from the National Kidney Foundation Council of Advanced Practitioners, data were collected and analyzed over the past decade. Results: Surveys of nephrology practitioners show the evolution of the dialysis-centralized practitioner to one encompassing all aspects of nephrology: hospital, intensive care unit, research, office, and all types of dialysis. Salaries and benefits have increased to compensate for the expansion of responsibilities. Implications for practice: Physician assistants and NPs in nephrology have the opportunity to use their skills and training in caring for this high-risk population.